CARDIOPULMONARY RESSUSCITATION IN PATIENTS WITH COVID-19 DURING PERIOPERATIVE PERIOD - Fernando da Luz, Vinícius; Silva, Wallace Andrino (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
The incidence of symptomatic patients diagnosed with COVID-19 who require hospitalization has been increased. Among these, there are patients who need to undergo surgical procedures. Anesthetic-surgical stress increases morbidity and the risk of adverse events, which can culminate in the Cardiorespiratory Arrest event. During the cardiopulmonary resuscitation (CPR), direct contact with the patient, chest compression, positive pressure manual ventilation and advanced airway management involve exposure of professionals to large amounts of aerosols and secretions. Furthermore, viral particles can remain suspended in the air of the operating room for up to three hours. Thus, monitoring of potentially serious patients, prevention and specific CPR protocols for patients with COVID-19 are important in the perioperative context.